A Case Study on Application of Rainwater Harvesting System for Different Towns as an Alternative Water Supply - NIK MAHMOOD, NIK NAZIERAH; ABU TALIB, SITI HIDAYAH (Recent Trends in Civil Engineering and Built Environment, 2022)
Rainwater Harvesting System (RWHS) is a reliable method used to collect rainwater into the defined catchment area. As water scarcity and flood problem sometimes hit the community, thus this system will act as one of the alternative ways in order to reduce the stated problems. Rainwater that precipitates will not be let to runoff on the ground surface instead we store it for an emergency usage. Hence, the objectives of this research are to determine the capacity of rainwater collected through RWHS as an alternative resource for water supply and to analyze the performance of harvested rainwater over water demand for different towns based on existing data. In order to achieve the objectives, some assessments and data extracted from previous research have been done such as rainfall data and water consumption for domestic usage. As a result, few towns have been analyzed on the performance of water collected and it showed that rainwater collected could be able to support the residents for their domestic water demand as for 20-30 percent. As a conclusion, this method could somehow give positive impact to the water consumers and thus efforts on increasing awareness and give more information on this system must be widen.